Prokrastinasi Akademik Mahasiswa Dalam Menyelesaikan Tugas Akhir - Ratna Sari; Zakaria AB; Wan Chalidaziah (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2020)
This study discusses how the level of student academic procrastination in completing the final project is motivated by the existence of internal factors and external factors that exist in students. The purpose of this study was to see how the students' academic procrastination in completing their final project. The research design used is a descriptive quantitative approach. The population in this study were students of BKI FUAD IAIN Langsa who had passed the minimum threshold for completion of the study period. In this study, data collection using an academic procrastination questionnaire with r= 9.00. The results showed that students had a variety of academic procrastination. Medium procrastination was 64 people 52.3%, while in the high category there were 57 people 46.34%, some other students were in the very high category as many as 2 people 1.63%, while in the low and very low category, namely 0 %. Overall, the students' academic procrastination was in the medium category with an average score of 53.37%. Based on the results of the research obtained, it shows that final year students need to be given treatment in order to be able to overcome the procrastination they have.